An Analysis and Prevention of Flyrock Accidents in Surface Blasting Operations - Harry C. Verakis; Thomas E. Lobb (International Society of Explosives Engineers, 2004)
Blasting is a primary means of extracting minerals and ores at surface mining operations. The domestic consumption of explosives and blasting agents during the year 2001 was about 5.25 billion pounds. Flyrock is always a major concern for the blaster. Flyrock from surface blasting operations has caused serious injury and death to employees and other persons. Injuries due to flyrock and the lack of blast area security accounted for over two-thirds of all blasting-related injuries in surface coal, metal, and nonmetal mines during the period 1978-2002. Selected accidents due to flyrock and lack of blast area security in surface mining are presented in this paper. Incidents related to construction blasting are also described. Techniques to mitigate blasting accidents are discussed. These include proper blast design, driller-blaster communication, inspection prior to loading and firing the blast, removing employees from the blast area, controlling access to the blast area, and using a blasting shelter. An experienced driller could detect potential problem areas such as voids, mud seams, incompetent rocks, and other irregularities by observing the progress of drilling. The drill log should include the details of any unusual or exceptional circumstances noticed during drilling. A blaster may need to alter the loading configuration to alleviate potential problems. Basic blast design is sometimes taken for granted and assumed to be proper for the conditions encountered, but one size does not fit all. It is known from the physics of blasting that the explosive energy takes the path of least resistance. The path of least resistance could generate flyrock, depending on the blast site conditions. A combination of ‘borehole tracking’ and ‘laser profiling’ can assist in improving the design of a blast. The blaster can use these tools to adjust borehole loading to match site conditions.